Structural study of G-rich sequences: G4, non-G4 and G-wires - Tan, Keith Wei Rong (Nanyang Technological University, 2023)
The study of nucleic acids is essential in understanding genetics as they are the very foundation of life as we know it. In our study, we aim to uncover more about the structure and interactions of Guanine-rich nucleic acids. We look at them with different means, mainly by nuclear magnetic resonance (NMR), ultraviolet absorption (UV) spectroscopy, circular dichroism spectroscopy (CD) and gel electrophoresis. With the spectroscopic techniques, we break the original assumption that only G-quadruplexes form in a G-quadruplex forming sequence by showing the presence of an unreported species, the non-G4 species. Lastly, with the aid of gel electrophoresis, we demonstrate that G-wires, another structure that can be formed by G-rich sequences are more stable than G-quadruplexes.